2002
DOI: 10.3354/dao049221
|View full text |Cite
|
Sign up to set email alerts
|

Comparative susceptibility of veliger larvae of four bivalve mollusks to a Vibrio alginolyticus strain

Abstract: The susceptibility of 7 d old veliger larvae of the scallops Argopecten ventricosus and Nodipecten subnodosus, the penshell Atrina maura, and the Pacific oyster Crassostrea gigas to a pathogenic strain of Vibrio alginolyticus was investigated by challenging the larvae with different bacterial concentrations in a semi-static assay. The results indicate that the larvae of the 2 scallop species are more susceptible to the V. alginolyticus strain than those of the oyster and the penshell. Signs of the disease were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 13 publications
1
34
0
2
Order By: Relevance
“…Sin embargo, al igual que en otros bivalvos, la alta mortalidad que se presenta durante la etapa larvaria y juvenil, es el principal problema que limita el desarrollo del cultivo en el laboratorio. Las mortalidades de C. corteziensis, son generalmente provocadas por bacterias del género Vibrio como ocurre también en Argopecten purpuratus (Riquelme et al 1995), A. ventricosus, Nodipecten subnodosus y Atrina maura (Luna-González et al 2002), C. virginica (Elston & Leibovitz 1980, Gómez-León et al 2008, C. gigas (Sugumar et al 1998, Luna-González et al 2002, Pecten maximus (Lambert et al 1999), Ruditapes philippinarum (Borrego et al 1996, Abasolo-Pacheco et al 2009). …”
unclassified
“…Sin embargo, al igual que en otros bivalvos, la alta mortalidad que se presenta durante la etapa larvaria y juvenil, es el principal problema que limita el desarrollo del cultivo en el laboratorio. Las mortalidades de C. corteziensis, son generalmente provocadas por bacterias del género Vibrio como ocurre también en Argopecten purpuratus (Riquelme et al 1995), A. ventricosus, Nodipecten subnodosus y Atrina maura (Luna-González et al 2002), C. virginica (Elston & Leibovitz 1980, Gómez-León et al 2008, C. gigas (Sugumar et al 1998, Luna-González et al 2002, Pecten maximus (Lambert et al 1999), Ruditapes philippinarum (Borrego et al 1996, Abasolo-Pacheco et al 2009). …”
unclassified
“…Interestingly, this temperature‐dependent disease resistance disappeared at the Pediveliger stage. In particular, Pacific oyster larvae are hypothesized to have a strong innate immune system that has a faster maturation rate in contrast to other marine bivalves (Luna‐Gonzalez, Maeda‐Martinez, Sainz, & Ascencio‐Valle, ). Thus, we hypothesize that in Pediveliger larvae the maturation of the immune system has reached a stage where temperature has no significant effect on defence capabilities anymore.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, they demonstrated its virulence for larvae of M. mercenaria , O. edulis , A. irradians and T. navalis . Luna-González et al (2002) reported that scallops ( Argopecten ventricosus and Nodipecten subnodosus ) were more susceptible to the pathogen than other species tested, including Atrina maura and C. gigas , whereas Gómez-León et al (2005) demonstrated the virulence of V. alginolyticus for carpet shell clam ( Ruditapes decussatus ) larvae and spat. On the other hand, Estes et al (2004) associated the degree of virulence, at least for C. gigas , with an increase in the water temperature.…”
Section: Overview Of the Pathogenic Vibrios For Bivalve Larvae And Spmentioning
confidence: 99%